Pharmaceutical therapy of Q-wave acute myocardial infarction: effects on adrenal morphology and function - Yu. V. Rogovskaya; Yu. M. Paderov; A. N. Repin; A. A. Sidelnikov (Российский кардиологический журнал, 2008)
Adrenal morphology and function were studied in intensively treated patients with Q-wave acute myocardial infarction (AMI). Adequate analgetic and thrombolytic therapy, as well as beta-adrenoblocker treatment, prevented adrenal medulla depletion. Contralateral adrenal reaction was heterogeneous. The results obtained provide a better understanding of adaptive reactions and medication action mechanisms in intensively treated patients with Q-wave AMI.